Pathogen-Derived Nucleases: An Effective Weapon for Escaping Extracellular Traps - Liao, Chengshui; Mao, Fuchao; Qian, Man; Wang, Xiaoli (Frontiers in Immunology, 2022)
Since the 2004 publication of the first study describing extracellular traps (ETs) from human neutrophils, several reports have shown the presence of ETs in a variety of different animals and plants. ETs perform two important functions of immobilizing and killing invading microbes and are considered a novel part of the phagocytosis-independent, innate immune extracellular defense system. However, several pathogens can release nucleases that degrade the DNA backbone of ETs, reducing their effectiveness and resulting in increased pathogenicity. In this review, we examined the relevant literature and summarized the results on bacterial and fungal pathogens and parasites that produce nucleases to evade the ET-mediated host antimicrobial mechanism.